Unlocking the Potential of Freight Logistics in India - Aritua, Bernard (World Bank, Washington, DC, 2017)
New, comprehensive analysis of data on the current routing of goods in India have positioned the country to break through its freight transport gridlocks and logistics inefficiencies. With a growth rate of more than 7 percent since 2014, India is the fastest growing major economy in the world. But as a share of its GDP, its logistics costs for moving freight are as high as 14 percentpercent of GDP, markedly more than the 8–10 percent for most advanced economies. The gap arises from excess costs generated by inefficiencies in the transport system, greater costs of storage and inventory and procedural delays. Closing that gap would give a major boost to India’s growth prospects. Studies of logistics improvements in advanced economies have shown that, with sufficiently detailed data on freight flows, targeted interventions in specific corridors andsubsectors can enable transformational changes in freight logistics performance. Researchersand logistics experts from the World Bank and South Africa’s Stellenbosch University have assembled and modeled such data for India, identifying bottlenecks and opportunities for morestrategic investment and collocation of activities to achieve production synergies and lower thecosts of logistics and trade.